Biotechnology Module Based on Sociosaintific Issues to Improve Student's Critical Thinking Ability Through Online Learning - Alfitriyani, Nia; Pursitasari, Indarini Dwi; Kurniasih, Surti (Jurnal Pendidikan Matematika dan IPA, 2021)
This research aims to develop a science learning module based on Socio Scientific Issues on biotechnology materials that can improve students' critical thinking skills. This research is an R&D research with a 4-D design. Validation is carried out by science experts and teachers. The module readability test and the students' responses to the module were obtained using a close test and questionnaire. Data analysis was performed descriptively quantitatively. The results of the module validation by expert lecturers obtained 89% and an average CVI value of 0.98 with a very valid category and was suitable for use. The module readability test results were 42.22% with the instructional level category indicating that the modules needed to be learned. The results of the N-Gain test for critical thinking ability is 0.59, the module is in the moderate category and the students' response value to the module by 87.50% showed the response in the very good category to the use of module-based SSI in learning to improve critical thinking skill.